Resolving the spatial scales of mass and heat transfer in direct plasma sources for activating liquids - Silsby, J. A.; Dickenson, A.; Walsh, J. L.; Hasan, M. I. (Frontiers in Physics, 2022)
When plasma is in direct contact with liquid, an exchange of mass and heat between the two media occurs, manifested in multiple physical processes such as vaporization and multiphase heat transfer. These phenomena significantly influence the conditions at the plasma liquid interface and interfere with other processes such as the multiphase transport of reactive species across the interface. In this work, an experimentally validated computational model was developed and used to quantify mass and energy exchange processes at a plasma-liquid interface. In the liquid side of the interface, it was shown that a thin film of liquid exists where the temperature is approximately three times higher than the bulk temperature, extending to a depth of 10 m. As the depth increased a strongly nonlinear decrease in the temperature was encountered. In the plasma side of the interface, plasma heating caused background gas rarefaction, resulting in a 15% reduction in gas density compared to ambient conditions. The combined effect of gas rarefaction and liquid heating promoted vaporization which increased liquid vapor density in the plasma phase. When water is the treated liquid, it is shown that water vapor constitutes up to 30% of the total gas composition in the region up to 0.1 mm from the interface, with this percentage approaching 70 to 80% of the total gas composition when the water’s temperature reaches its boiling point.